Jeremy Bentham’s Utilitarianism Theory Methodology in the Corporation Law System In Indonesia - Boy Aditya Prakasa; Elisatris Gultom (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study examines the relevance and application of Jeremy Bentham's theory of utilitarianism in the context of corporate law in Indonesia. The theory of utilitarianism, based on the principle of "the greatest happiness for the greatest number", offers a moral framework oriented towards social benefit. In practice, corporate law is often faced with an ethical dilemma between the interests of shareholders and the public welfare. The research method used is a normative juridical approach with qualitative analysis of laws and regulations related to corporations in Indonesia, as well as a literature study of primary and secondary literature on utilitarianism theory and legal ethics. The results show that most of the corporate regulations in Indonesia, such as the Limited Liability Company Law and the Financial Services Authority regulations, implicitly reflect utilitarian values, especially in the aspects of corporate social responsibility (CSR) and consumer protection. However, there is still a gap between legal norms and practical implementation that has an impact on the inequality of benefit distribution. In this study, it emphasizes the importance of strengthening utilitarian ethics in the formulation and implementation of corporate legal policies, in order to create a legal order that not only benefits business actors, but also provides the greatest benefits to the wider community.